2008
DOI: 10.1111/j.1572-0241.2007.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

New Design Esophageal Stents for the Palliation of Dysphagia From Esophageal or Gastric Cardia Cancer: A Randomized Trial

Abstract: All three stents are safe and offer adequate palliation of dysphagia from esophageal or gastric cardia cancer. Nonetheless, Polyflex stents seem the least preferable in this patient group, as placement of this device is technically demanding and associated with a high rate of stent migrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(181 citation statements)
references
References 18 publications
10
165
2
4
Order By: Relevance
“…The Niti-S stent (Taewoong Medical Inc, Seoul, Korea) was designed with flares to 26 mm at both ends and a double-layer configuration comprising an inner polyurethane layer to prevent tumor ingrowth and an outer uncovered nitinol-wire tube to allow the mesh of the stent to embed itself in the esophageal wall [30]. In a recent randomized prospective trial, recurrent dysphagia due to stent migration was less frequently seen with the Niti-S stent (12%) than with the Ultraflex (17%) or Polyflex (29%) stent [31]. We prefer to use the Ultraflex stent with a diameter of 18/23 mm, which, similar to other stents [21,32], is available with uncovered proximal and distal segments, allowing the normal mucosa above and below the tumor to project into the stent lumen.…”
Section: Discussionmentioning
confidence: 98%
“…The Niti-S stent (Taewoong Medical Inc, Seoul, Korea) was designed with flares to 26 mm at both ends and a double-layer configuration comprising an inner polyurethane layer to prevent tumor ingrowth and an outer uncovered nitinol-wire tube to allow the mesh of the stent to embed itself in the esophageal wall [30]. In a recent randomized prospective trial, recurrent dysphagia due to stent migration was less frequently seen with the Niti-S stent (12%) than with the Ultraflex (17%) or Polyflex (29%) stent [31]. We prefer to use the Ultraflex stent with a diameter of 18/23 mm, which, similar to other stents [21,32], is available with uncovered proximal and distal segments, allowing the normal mucosa above and below the tumor to project into the stent lumen.…”
Section: Discussionmentioning
confidence: 98%
“…Median DSs typically decreased by two levels when lccSEMS were placed (22,23,(33)(34)(35). Median DSs in our sccSEMS patients decreased by only one level.…”
Section: Discussionmentioning
confidence: 98%
“…Major AEs (severe pain, hemorrhage, fever, and fistula) occurred in 20% of patients, minor AEs in 22%, and stent related deaths in 7%. Prospective studies of lccSEMS of different design from other manufactures have revealed similar AE rates (13,22,33). In the current 31 patient sccSEMS study, major AEs occurred in 6.5% of patients, minor AEs in 19.4%, and stent related deaths in no patients.…”
mentioning
confidence: 99%
“…Diese leichte Entfernbarkeit wird mit einer hohen Migrationsrate «erkauft» (etwa 25%) [65]. In 2 prospektiven, randomisierten Studien [66,67], bei denen der Polyflexstent mit dem Ultraflexstent verglichen wurde, konnte zwar eine etwa gleich gute Reduktion der Dysphagie erzielt werden, aber die Komplikationsrate des Polyflexstents von bis zu knapp 50% war in beiden Studien signifikant höher als die des Ultraflexstents. Hauptkomplikation war die Stentmigration.…”
Section: Selbstexpandierende Plastikstentsunclassified